Proceedings of the 1st International Conference on Economics, Business, Entrepreneurship, and Finance (ICEBEF 2018) 2019
DOI: 10.2991/icebef-18.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention Analysis on E-Money Services in Indonesia: Using the modified UTAUT model

Abstract: The level of use of e-money services in Indonesia is still relatively low. Low in trust and high risk are thought to be determinants of the level of community behavioral intention. On the other hand, other factors of age, gender and level of education also affect the relationship of behavioral intention with the determinants. The purpose of this study is to determine the effect of the dimensions of trust (multi dimensional trust) and perceived risk on the intention of people's behavior on e-money services in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…This indicates that one or several domains from an established and widely applied basic framework, in this case, TPB and UTAUT, still provide consistent results. Analysis in the context of the use of e-money as a means of payment transactions consistently supports previous research results, i.e., that social factors and effort expectancy are predictors of behavior [26,27,44,47,48,52]. This means that customers will continue to use e-money, make it the first choice of payment, and keep the installed e-money application on smart devices because of external persuasion such as shops that they visit and close friends or family as social factors.…”
Section: Model Evaluationsupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that one or several domains from an established and widely applied basic framework, in this case, TPB and UTAUT, still provide consistent results. Analysis in the context of the use of e-money as a means of payment transactions consistently supports previous research results, i.e., that social factors and effort expectancy are predictors of behavior [26,27,44,47,48,52]. This means that customers will continue to use e-money, make it the first choice of payment, and keep the installed e-money application on smart devices because of external persuasion such as shops that they visit and close friends or family as social factors.…”
Section: Model Evaluationsupporting
confidence: 82%
“…For example, in the case of online shopping, it was stated that shopping behavior online or through the internet was influenced by a person's attitude towards the shopping system [44,45] in the context of mobile banking adoption [46], use of non-cash systems [27], and adoption of smart home technology [47]. More specifically, it supports research carried out in the context of the use of electronic payments, mobile payments, the use of e-money, and similar topics [48,49].…”
Section: Model Evaluationmentioning
confidence: 87%
“…Previous studies from , Perceived trust has a positive relationship between attitude and as well as Perceived ease of use toward using on mobile payment and intensity of using mobile payment, this is also supported by another study (Islam et al, 2020). However, based on his finding, Perceived trust negatively influences the user's perceived risk, which this also supported in other studies (Cabanillas, Leiva, et al, 2016;Giri et al, 2019). The results offer support that trust affecting the intention to use e-payment services.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 77%
“…Perceived trust in mobile payment negatively influences the user's Perceived of risk towards it (p = 0,035; t =2,111). There is an empirical study to support this Hypothesis, as shown in the research of Santosa et al (2021), Cabanillas, Leiva, et al (2016), and Giri et al (2019.…”
Section: Statistics P Values Resultsmentioning
confidence: 87%
“…The results of this study indicate that all the moderating variables adopted for this research, which included gender, age and experience, did not affect any of the 13 factors identified as influencing factors for GPs’ acceptance of CDSS. Several studies have similarly indicated the minimal effect or non-impact of these variables on users’ acceptance of technological systems, while other studies have indicated more particularly that age does not affect acceptance of IT (Giri, Apriliani, and Sofia, 2019; Gusman and Ariyanti, 2019), and some have indicated that gender does not affect acceptance of IT (Giri et al, 2019; Gusman and Ariyanti, 2019). Some researchers have also asserted that experience does not affect technology acceptance (Alasmari and Zhang, 2019; Harmandaoglu Baz, Cephe, and Balçikanli, 2019).…”
Section: Resultsmentioning
confidence: 99%